Nationality Policing Model for the Revival of Indonesian Hizbut Tahrir Transnationalism in the Legal Territory of the Bogor Police - Fathoni Riza (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine the National Police model for the revival of Indonesian Hizbut Tahrir (HTI) transnationalism as an asymmetric security threat in the jurisdiction of the Bogor Police, which is the task of the National Police in maintaining the existence of Pancasila as the Indonesian national ideology. The phenomena had implications for the stability of domestic security as a prerequisite for achieving the ideals of national development within the framework of a democratic rule of law. National policing is expected to be an effort by the police at the management and operational levels to achieve social order, which is achieved either with or without coercive efforts, through synergy with stakeholders and active community involvement. The next purpose was to achieve the goal of strengthening nationality based on love for the homeland and nation and overcoming security threats based on national ideology that can threaten the existence of the Pancasila as Indonesian people’s national ideology.